2021
DOI: 10.1186/s12871-021-01271-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anxiety predicted the incidence of postoperative delirium in patients undergoing total hip arthroplasty: a prospective cohort study

Abstract: Background Delirium was characterized with a series of symptoms of a sudden onset of disturbances in attention, a loss in memory loss and defects in other cognitive abilities that were also appeared in the syndrome of anxiety. Even though there are overlapped clinical symptoms existed in anxiety and delirium, the relationship between anxiety and delirium was still unclear. The propose of this study was to investigated the effect of preoperative anxiety on postoperative delirium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 50 publications
1
29
0
2
Order By: Relevance
“…Most episodes of POD were registered on the first or second postoperative day, which is in line with previous studies (Chaiwat et al, 2019 ; Saravana‐Bawan et al, 2019 ) describing a higher risk of developing POD during the first 72 hr after surgery. The median POD duration identified in this study was 1 day, which is in line with results from geriatric ortho‐geriatric populations (Ma et al, 2021 ). Yet, in very specific cohorts, such as cardiac‐surgery patients, the mean POD duration was 2.5 days (Koster et al, 2009 ).…”
Section: Discussionsupporting
confidence: 91%
“…Most episodes of POD were registered on the first or second postoperative day, which is in line with previous studies (Chaiwat et al, 2019 ; Saravana‐Bawan et al, 2019 ) describing a higher risk of developing POD during the first 72 hr after surgery. The median POD duration identified in this study was 1 day, which is in line with results from geriatric ortho‐geriatric populations (Ma et al, 2021 ). Yet, in very specific cohorts, such as cardiac‐surgery patients, the mean POD duration was 2.5 days (Koster et al, 2009 ).…”
Section: Discussionsupporting
confidence: 91%
“…Besides poor clinical outcome, preoperative anxiety in THA increases the risk of postoperative delirium [ 29 ]. Anxiety and depression not only influence individual patient recovery but also hospital and personal costs and those incurred by premature retirement and loss of employment [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported education was not associated with POD risk ( Cavallari et al 2016 , 2017 ; Cizginer et al 2017 ; Hshiesh et al 2017 ; Inouye et al 2016 ; Tripp et al 2021 ; Vasunilashorn et al 2017 ). Another large study, the PAWEL study based in Germany ( Deeken et al 2022 ), as well as smaller cohort studies from Europe, Asia, and South America support these null results ( Jiang et al 2017 ; Kazmierski et al 2013 ; Mahanna-Gabrielli et al 2020 ; Puustinen et al 2016 ; Ristescu et al 2021 ; Sauer et al 2017 ; Seo et al 2014 ; Xue et al 2016 ), whereas other investigations do suggest a low education as a risk factor for POD ( Dworkin et al 2016 ; Gu et al 2021 ; Guan et al 2021 ; Huang et al 2021 ; Ma et al 2021 ; McAlpine et al 2008 ; Ordóñez-Velasco and Hernández-Leiva 2021 ; Schoen et al 2011 ; Sprung et al 2017 ; Su et al 2019 ; Tenpaku et al 2021 ; Tobar et al 2018 ). Interestingly, one recent Chinese study of 323 laryngectomy patients reported evidence in the opposite direction.…”
Section: Cognitive Epidemiology In a Surgical Settingmentioning
confidence: 97%